Theasaponin E1 as an effective ingredient for anti-angiogenesis and anti-obesity effects. Issue 2 (1st February 2014) - Kim, Jong-Deog; Chaudhary, Narendra; Seo, Hyo-Jin; Kim, Min-Yong; Shin, Tai-Sun
Abstract: Theasaponin E1 (TSE1 ) has been suggested to have higher biological activity than other saponins present in tea seed. Saponins have recently been considered as a potential chemotherapeutic agent for treating cancer. We examined the anti-angiogenic and anti-obesity properties of TSE1 contributing to anti-cancer efficacy. Treating with a 10 μg/mL concentration of TSE1 completely inhibited tube formation in human umbilical vein endothelial cells (HUVECs). TSE1 showed toxicity toward cancer cells and inhibited in vivo growth of the tumor. The vascular endothelial growth factor (VEGF) receptor complex was suppressed, leading to the inhibition of protein kinase B (Akt) expression and down-regulation of nuclear factor-kappa B (NF-kB) activation. The differentiating 3T3-L1 cells treated with TSE1 had decreased lipid droplet formation measured by Oil Red O staining. Reduced weight was measured in mice fed with a TSE1 plus high-fat diet. The results taken together, and particularly the NF-kB inhibition, suggest that TSE1 may have multi-target action for treating cancer as a novel chemotherapeutic agent. Graphical abstract: : Bioactive theasaponin E1 (TSE1 ) suppresses multi-component receptor complex by inhibition of AKT and PI3K, leading to suppressive effect on NF-κB expression.